2018
DOI: 10.12659/msm.909458
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-495 Confers Increased Sensitivity to Chemotherapeutic Agents in Gastric Cancer via the Mammalian Target of Rapamycin (mTOR) Signaling Pathway by Interacting with Human Epidermal Growth Factor Receptor 2 (ERBB2)

Abstract: BackgroundIn recent years, the incidence of gastric cancer (GC) has been increasing worldwide. Emerging evidence shows that microRNAs (miRs) may be involved in the pathogenesis of GC. Thus, this study explored the mediatory role of miR-495 in GC chemosensitivity, and investigated the mechanism by which it affects the biological behaviors of GC cells via the mTOR signaling pathway.Material/MethodsAfter GC and paracancerous tissue collection, the positive rate of ERBB2 and mTOR was evaluated by immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Evidence has demonstrated that miRNAs initiate or suppress cancer development by regulating cell proliferation, metastasis, apoptosis or differentiation (10). For example, miR-495 regulates the progression of gastric cancer via the mammalian target of rapamycin pathway (11). miR-150 suppresses thyroid cancer development by modulating Ras-related protein Rab-11A/WNT/β-Catenin signaling (12).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has demonstrated that miRNAs initiate or suppress cancer development by regulating cell proliferation, metastasis, apoptosis or differentiation (10). For example, miR-495 regulates the progression of gastric cancer via the mammalian target of rapamycin pathway (11). miR-150 suppresses thyroid cancer development by modulating Ras-related protein Rab-11A/WNT/β-Catenin signaling (12).…”
Section: Introductionmentioning
confidence: 99%
“…HSPA8 is highly involved in many biological processes, including proteasomal degradation [ 35 ], catalyzing protein folding and clathrin uncoating [ 36 ], and other protein networks involved in protein catabolism, protein homeostasis, ubiquitination, carbohydrate metabolism and cell cycle control [ 37 ]. ERBB2 is a member of a family of transmembrane receptor tyrosine kinases involved in the regulation of cellular processes by modulation of several pathways, such as mTOR, MAPK, and PI3K/AKT pathways [ 38 , 39 , 40 ]. In consistent with the present study, the functional role of ERBB2 on milk production traits has been also identified as positional candidate gene for lactation persistency in Canadian Holstein cattle [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, it was also determined that miR-486–5p combined with cisplatin could induce caspase-9 and -3, as well as p53, while suppressed the anti-apoptotic genes sirtuin 1 (SIRT1), olfactomedin 4 (OLFM4), SMAD4, and Bcl-2. Thus, it can be concluded that miR-486–5p mimic can help cisplatin to exert more efficient apoptotic effects on BC cell [ [92] , [93] , [94] ]. In detail, apoptosis induction caused by concurrent administration of this miRNA mimic and cisplatin chemo drug is primarily regulated through subG1 phase arrest during the cell cycle [ 91 ].…”
Section: Non-coding Rnas In Regulation Of Cisplatin Chemo-resistance ...mentioning
confidence: 99%